2023
DOI: 10.1007/s10984-023-09459-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing students’ and teachers’ perceptions about teachers’ interpersonal behaviour in Greek secondary education

Abstract: AbstractΤeachers’ interpersonal behaviour is considered important for the quality of the student–teacher relationship. The present study examined teachers’ and students’ perceptions regarding teachers’ interpersonal behaviour and the degree of their agreement at the class level. Moreover, this study investigated whether possible differences between them are associated with the teachers’ and classes’ characteristics. Participants were 1669 students and 43 secondary teachers within 85 secondary classrooms in Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The research results indicated that there is a significant difference between teachers' self–perceptions and students' perceptions of teacher interpersonal behavior. The differences among teachers' and students' perceptions can partially be explained by teachers' years of teaching experience and the degree level, as well as the class educational level (Karamane et al, 2023 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research results indicated that there is a significant difference between teachers' self–perceptions and students' perceptions of teacher interpersonal behavior. The differences among teachers' and students' perceptions can partially be explained by teachers' years of teaching experience and the degree level, as well as the class educational level (Karamane et al, 2023 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through teachers' perception, they can see their thoughts and feelings, especially when defining their actions (Donker et al, 2021). Teachers' perspectives are ineffective if they are the only source of information in examining classroom processes (Karamane et al, 2023). This is because it is possible that teachers are not aware of what they have done (Scherzinger & Wettstein, 2019).…”
Section: Introduce the Problemmentioning
confidence: 99%
“…Therefore, in vocational schools, learning environments strongly differ from other schools not only because of the higher proportion of male teachers, but also because of the high proportion of ethnic minority students. Teachers often adjust their behavior according to the learning group (Levy et al, 1997), but might not be aware of their behavior (Scherzinger & Wettstein, 2019), and sometimes they perceive their behaviors in a biased way (Karamane et al, 2023). This often is true for ethnic minority students' perceptions of teacher behavior (den Brok et al, 2003;Levy et al, 1997).…”
Section: Introductionmentioning
confidence: 99%